Uma experiência de educação patrimonial na cidade de João Pessoa: o processo de elaboração das cartilhas do patrimônio pelo IPHAEP - Targino, Maria Ivonilde Mendonça (2007)
This study recovers the process of elaboration/production of the Cartilha do Patrimônio: Centro Histórico de João Pessoa (Patrimony booklet: Historical Center of João Pessoa), edited by the Institute for Artistic and Historical Patrimony of the State of Paraíba (IPHAEP), in 2002 and 2003, since the its initial project, in the 1980 s, until its actual use in schools, in the beginning of the academic year of 2003, as a pioneering initiative of the state of Paraíba. Its thematic focus is on the historical development of the notion of heritage ( patrimonial ) education and its pedagogical tools, in governmental institutions for cultural patrimony preservation, at state level as much as national level. This research did not carry out a quantitative fact-gathering to measure the reach and efficacy of the program, that could subsidize an evaluation of its repercussion in public policies for preservation. It analyses historically the process and its context, consulting public documents, the existing bibliography about the subject and, using oral history methodology, collected participant people statements - live testimonies in order to deepen the reflection about that experience. The two editions of the booklet were analyzed, aiming at the identification of the reasons and meanings of that educational material, as both practice of preservation and tool for cultural literacy, carried out by the institution (IPHAEP) in connection with the public schools, according to the Demarcation of the Historical Center and Heritage Education. The study wants to contribute in finding answers to the questionings on the importance of patrimonial preservation for history and the potentiality of cultural patrimony to support society in the construction of its historicity and identity. This reflexion on preservation in its historical context should give us a better understanding of how Historical Culture is generated. Emphasis is given to the importance of Memory for the configuration of Cultural Patrimony and to the necessary insertion of related themes in the program of history teaching in formal education.